What's in It for Me? or Motivation and Communication - Harold B. Swanson (Journal of Applied Communications, 1975)
What's in it for me? What stake do I have in this? Sound like selfish, self-centered questions? Indeed they may be, but they are questions we must answer for our audiences as we communicate as scientists, educators, communications specialists.